THE EFFECTIVENESS OF MIRROR THERAPY IN MOTOR AND FUNCTIONAL RECOVERY PROCESS IN PATIENTS WITH STROKE - Silva, Aline Alves da; Vieira, Kleber Sulpino (Journal of Health Care, 2017)
Introduction: Loss of motor function of the upper limb is one of the most debilitating deficits after a stroke. Mirror therapy aims to increase motor function through functional activities and promote cortical reorganization through visual feedback. Objective: To investigate the efficacy of mirror therapy on motor function improvement of patients with stroke. Methods: The research was performed through the review of scientific articles available in the electronic databases PeDro, PubMed, SciELO, PsychInfo, Science Direct, and Lilacs, published between 2007 and 2017. The inclusion criteria were: clinical case studies, randomized controlled trials related to the Mirror Neuron Theory, and the efficacy of mirror therapy in motor and functional recovery of upper limb in female and male participants older than 18 years and diagnosed with ischemic stroke with up to two years of injury. Results: Twelve studies were included in this review, with a total of 214 participants, in which mirror therapy was compared with other interventions. Manual dexterity and motor function of the upper limb were often measured before and after the intervention. Conclusion: Mirror therapy has shown benefits for motor recovery and sensory-motor function when performed alone or in combination with conventional therapy in acute, subacute, and chronic ischemic stroke patients. Effects on motor function were maintained at the assessment after 6 months.